THE ROLE AND IMPORTANCE OF PARENTAL AFFECTION IN CHILD DEVELOPMENT. RESULTS OF JOHN BOULBY'S RESEARCH - Rimbayeva Ozoda Bazarbayevna (Western European Studies, 2024)
the role of the parent is incomparable for the child to develop throughout his life. The child will be permanently connected to the mother even during the perenatal period before birth. Even during the fetal period, the child receives information and influences from the external environment through his mother. If the negative impact on her mother bothers her, the positive impact will calm her down. This article will talk about the role and importance of parents in Child Development, how their attention and affection affect child development
Keywords: child; perenatal; postnatal; developmental